Towards a holistic view of customer value creation in Lean: A design science approach - Erdoægan Gülyaz; Jack A. van der Veen; Venu Venugopal; Sam Solaimani (Cogent Business & Management, 2019)
While 'identifying customer value' is the first principle of Lean thinking, the concept of customer value has largely remained unchanged in the Lean discourse - quality, cost and delivery. This research examines the problem of working from such an internal process point of view in today's highly dynamic world, where customer needs get increasingly more sophisticated. Aiming to contribute to solving this problem, this paper develops a new artifact, the so-called Customer Value Matrix (CVM) Instrument by bridging Operations Management, Strategy and Marketing literatures and following the design science approach. This paper builds the CVM instrument based on five theoretically grounded design principles, which are derived from a systematic review of 49 articles, and proposes three empirically grounded technological rules as a result of multi-stage evaluations. Supporting Service-Dominant Logic and Lean Consumption views, the CVM instrument can be considered as a novel addition to the Lean toolkit and enable managers to view what the customer truly values in a more holistic fashion and, as a result, promote a balanced view of process and customer focus.
Keywords: 650; Lean; customer value; service-dominant logic; design science research